THE COMPARISON ON THE STUDENTS’ PRONUNCIATION ACHIEVEMENT TAUGHT BY USING SONG AND VIDEO OF THE EAGLE ENGLISH COURSE PARE - kusuma, winda dyah (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 1 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Having been aware of the difficulties foreign language learners’ experience in pronunciation, this research decided to do whether comparing Song and Video to help students’ pronunciation achievement of the The Eagle English Course Pare. This study used quasi experimental design while devided into two classes. The stage was intermediate Class. There were 26 students, 13 students in Song Class and 13 students in Video Class. To know the result, this research gave six meeting of each classes. Meanwhile, to know the achievement the researcher used test and observed the result of test by computing t-test by using SPSS. The result of the study showed that the mean of Song class test is 71.15. While, the mean of Video class test is 70.38. Based on the mean of both classes, the criteria were in good criteria. Therefore, the nul hypothesis is accepted; the two samples are from the same population and there is no significant difference between two groups. This result implies that song and video were not significantly different in terms of their achievement after treatment.